Does neurotransmission impairment accompany aluminium neurotoxicity? - Goncalves, Paula P. (2007)
Neurobehavioral disorders, except their most overt form, tend to lie beyond the reach of clinicians. Presently, the use of molecular data in the decision-making processes is limited. However, as details of the mechanisms of neurotoxic action of aluminium become clearer, a more complete picture of possible molecular targets of aluminium can be anticipated, which promises better prediction of the neurotoxicological potential of aluminium exposure. In practical terms, a critical analysis of current data on the effects of aluminium on neurotransmission can be of great benefit due to the rapidly expanding knowledge of the neurotoxicological potential of aluminium. This review concludes that impairment of neurotransmission is a strong predictor of outcome in neurobehavioral disorders. Key questions and challenges for future research into aluminium neurotoxicity are also identified. (c) 2007 Elsevier Inc. All rights reserved.